Посягання на релігійні святині в історії кримінального права - Білаш, Олександр Володимирович; Билаш, Александр Владимирович; Bilash, Aleksandr (Одеса : Юрид. л-ра, 2012)
The Encroachment on religious relics in the history of the criminal law. — Article. Article is devoted research of history of development of the domestic legislation on crimes against religion. The basic stages of evolution of this institute are defined, in particular, concerning it is criminal-legal protection.
Білаш О. В. Посягання на релігійні святині в історії кримінального права / О. В. Білаш // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 626-631.
Keywords: кримінальне право; злочини проти віросповідання; святотатство; уголовное право; преступления против вероисповедания; criminal law; crimes against religion; sacrilege